2010
DOI: 10.1143/jpsjs.79sa.69
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Factor of Activation Energy for Ionic Conductivity in Perovskite-Type Lithium Ion-Conducting Oxides

Abstract: The predominant factors of the activation energy for ionic conductivity in perovskite-type lithium ion-conducting oxides were discussed in terms of structural distortion. As the result, the activation energies in almost all compounds are governed by a factor, a p /(B large -O) (a p : perovskite parameter (cube root of cell volume per formula unit), (B large -O) : inter-atomic distance between larger B ion and oxygen ion). This finding implies that (i) the larger B ion gives rise to structural distortion such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…These computational errors may be ascribed to (i) the used exchange-correlation functional, as reported by Han et al [21], who found that the PBE underestimates the stability of some of the halide perovskites; (ii) at finite temper ature in experiments, entropy contributions to free energies are not included in DFT calculations; (iii) dynamic stabilities are not considered in formation energy calculations. In comparison to the results of 31 types of existing perovskites in experiments [19, [22][23][24][25][26][27][28][29][30][31], we have found that 60 meV/atom is a proper border line in formation energies for separating stable and unstable perovskites, as shown in figure 4. Current thermodynamic stability calculations are performed on ground-state level by DFT calculations at 0 K. Previous calcul ations of hybrid halide perovskites at 300 K [32] showed that the entropies could contribute more for products (by 0-50 meV/atom) than that for reactants, thus stabilizing perovskite phases.…”
Section: Resultsmentioning
confidence: 51%
“…These computational errors may be ascribed to (i) the used exchange-correlation functional, as reported by Han et al [21], who found that the PBE underestimates the stability of some of the halide perovskites; (ii) at finite temper ature in experiments, entropy contributions to free energies are not included in DFT calculations; (iii) dynamic stabilities are not considered in formation energy calculations. In comparison to the results of 31 types of existing perovskites in experiments [19, [22][23][24][25][26][27][28][29][30][31], we have found that 60 meV/atom is a proper border line in formation energies for separating stable and unstable perovskites, as shown in figure 4. Current thermodynamic stability calculations are performed on ground-state level by DFT calculations at 0 K. Previous calcul ations of hybrid halide perovskites at 300 K [32] showed that the entropies could contribute more for products (by 0-50 meV/atom) than that for reactants, thus stabilizing perovskite phases.…”
Section: Resultsmentioning
confidence: 51%
“…Various activation energy parameters affect the properties of materials, such as the activation energies for ionic conductivity [1], surface self-diffusion [2], creep [3], oxidation [4], structural relaxation [5], crystallization [6], and permeation [7]. In particular, in hydrogen-separable membranes, the activation energy for hydrogen permeation is a crucial parameter affecting the hydrogen permeability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, Inaguma et al demonstrated that the decrease in the tilt angle due to ion substitution lowers the activation energy. 90 The two activation energies obtained by PFG-NMR analysis and the change in C Q observed in the static NMR spectra both support the change in the local environment with the change in the TiO 6 tilt angle. On the other hand, the cause of non-Arrhenius behavior remains under debate.…”
mentioning
confidence: 63%
“…Varez et al emphasized the relationship between the tilt angle of TiO 6 octahedra and the change in activation energy. , The rotational motion of TiO 6 promotes hopping of the Li + ions, and thus, the smaller the tilt angle, the lower the activation energy . Moreover, Inaguma et al demonstrated that the decrease in the tilt angle due to ion substitution lowers the activation energy . The two activation energies obtained by PFG-NMR analysis and the change in C Q observed in the static NMR spectra both support the change in the local environment with the change in the TiO 6 tilt angle.…”
Section: Resultsmentioning
confidence: 93%